1997
DOI: 10.1016/s0092-8674(00)80204-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure of RGS4 Bound to AlF4−-Activated Giα1: Stabilization of the Transition State for GTP Hydrolysis

Abstract: RGS proteins are GTPase activators for heterotrimeric G proteins. We report here the 2.8 A resolution crystal structure of the RGS protein RGS4 complexed with G(i alpha1)-Mg2+-GDP-AlF4 . Only the core domain of RGS4 is visible in the crystal. The core domain binds to the three switch regions of G(i alpha1), but does not contribute catalytic residues that directly interact with either GDP or AlF4-. Therefore, RGS4 appears to catalyze rapid hydrolysis of GTP primarily by stabilizing the switch regions of G(i alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
853
4
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 774 publications
(894 citation statements)
references
References 55 publications
(29 reference statements)
36
853
4
1
Order By: Relevance
“…The extreme N-terminal helix of Gaz is crucial for interaction with Rz proteins Wang et al, 1998). This interaction is not observed for Gai1 and RGS4 (Tesmer et al, 1997) and could account for the binding of GazGTP and not just of GazGDP.P to Rz proteins. RGS proteins attempt to synchronize the variations in agonistinduced receptor-activation and the number of Ga-GTP subunits that regulate effectors.…”
Section: Discussionmentioning
confidence: 94%
“…The extreme N-terminal helix of Gaz is crucial for interaction with Rz proteins Wang et al, 1998). This interaction is not observed for Gai1 and RGS4 (Tesmer et al, 1997) and could account for the binding of GazGTP and not just of GazGDP.P to Rz proteins. RGS proteins attempt to synchronize the variations in agonistinduced receptor-activation and the number of Ga-GTP subunits that regulate effectors.…”
Section: Discussionmentioning
confidence: 94%
“…However, the members of the RGS-Rz subfamily exhibit the distinctive feature of binding with similar affinities to the activated GaGTP subunits as well as to the transition state . This is accomplished through binding to the Nterminal helix of activated Ga subunits Wang et al, 1998), an interaction that is not observed between Gai and RGS4 (Tesmer et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Both are required for RGS binding to the transition state of Ga and for its subsequent GAP activity. The loops between a3 and a4, a5, and a6, and the residues at the end of a7 and at the beginning of the a8 helix form the Ga interaction surface (Tesmer et al, 1997). Other RGS residues not involved in contact with Ga may mediate RGS-effector interactions, as occurs in the RGS9-1 and phosphodiesterase (PDE)g-Gat complex.…”
Section: Discussionmentioning
confidence: 99%
“…The extreme N-terminal helix of Ga subunits is crucial for its interaction with RGS-Rz proteins (Wang et al, 1998;Tu et al, 1997). This interaction does not occur between Gai1 and RGS4 (Tesmer et al, 1997) and could account for the binding of GaGTP to RGS-Rz proteins. In this scenario, the capacity of certain RGS proteins to bind to receptor-activated GaGTP subunits could reduce Gamediated activation of downstream effectors.…”
Section: Discussionmentioning
confidence: 99%